(untitled) (European Journal of Economics, Finance and Business Development, 2026)
This article based on data from the World Bank and official national sources, a comparative analysis has been conducted on the structure, terms, yields, and allocation of proceeds of green bonds and sukuk in international practice. These findings provide an important theoretical and practical foundation for the development of the green sukuk market in Uzbekistan. The results of the study indicate that, despite the significant potential of green sukuk to attract capital and finance environmentally sustainable projects, several challenges remain in their implementation. In particular, risks such as greenwashing, the high cost of financial instruments, currency mismatches, and the insufficient development of the regulatory and legal framework constitute major barriers. The experience of Uzbekistan and developed countries demonstrates that properly structured and institutionally supported green sukuk, in compliance with Sharia principles, can serve as an effective instrument for mobilizing investment. In conclusion, it should be emphasized that the successful introduction of green sukuk in Uzbekistan requires the deepening of institutional reforms, ensuring transparency, improving the regulatory framework in line with international standards, and integrating this instrument into the country’s public financial policy.